Pocket investor - "Ryland, Philip" (London, 2010)
The investment business continues to become increasingly sophisticated by the day as new products are created, faster ways of selling them are established and trading levels grow steadily. In addition, the internet has transformed the way investment markets operate and has thrown out the rule book on how markets value companies operating in traditional sectors against those operating in fashionable new sectors. To anticipate the markets and profit from them now requires more skill and analysis than ever before. POCKET INVESTOR is a clear and lively guide through the complexities and jargon of the investment world. It contains concise essays on the returns you can expect from the market, cycles and bubbles, the internet effect; an A-Z of key terms concepts from Arbritrage Pricing Theory, Fibonacci numbers and Japanese candlesticks to Zero Coupon Bonds; wide-ranging appendices including long-term trends of share-price indicies, a comparison of returns on different investments over time, and suggestions for further reading.
Keywords: Investor